Laparoscopic Approach to Vesicovaginal Fistula: Our Experience - Mallikarjun Reddy, Shishir Devaraju, Murigenda Hiremath, Nerli R B* (Recent Research in Science and Technology, 2010)
Abstract Introduction: Most Vesicovaginal fistulasÂ  in the industrialized world are iatrogenic, Though they may also result from congenital anomalies, malignant disease, inflammation and infection, radiation therapy, iatrogenic (surgical) or external tissue trauma, ischemia, parturition and a variety of other processes. Vesicovaginal fistulas (VVF) represent, by far, the most common type of acquired fistula of the urinary tract. The goal of treatment of these fistulas is the rapid cessation of urine leakage with return of normal and complete urinary and genital function. Materials and Methods: Female patients presenting with iatrogenic Vesicovaginal fistula formed the study group. A detailed history and physical examination was carried out. Imaging included intravenous urogram, cystogram, computerised tomography, MR imaging and retrograde ureterogram as felt necessary.Â  Surgical repair of Vesicovaginal fistula was carried out through a laparoscopic approach. Results: 24 women presented with VVF, of these 19 underwent laparoscopic transperitoneal repair, whereas 5 underwent laparoscopic transvesicoscopic repair. The intraoperative blood loss was minimal (< 100 ml) and no major perioperative complications were noted. Conclusions: Minimally invasive approaches to repair vesico-vaginal fistulas are feasible, safe and associated with minimal blood loss, hospital stay and morbidity. Keywords: Laparoscopy, Minimally invasive, Vesicovaginal fistula